(untitled) (Homiletic, 2023)
This study examines digitally-mediated sermon listening practices by interviewing twenty-nine listeners from Swedish Protestant congregations. The analysis draws on Theodore Schatzki’s practice theory, focusing on the entanglement of human activity, material arrangements surrounding the preaching event, and the ends of practices—including how changes to any or all of the above impact the practice in question. The study found that listeners strove to uphold the listening practices they were accustomed to from their respective churches and attempted to carry these over into the digitally-mediated preaching event. To a large extent, they succeeded in opening and managing a “third room of preaching.” Furthermore, the study highlighted the importance of knowing the ends of these listening practices. The study also demonstrated the significance of material arrangements and how changes in these arrangements sometimes led to the obstruction—or even breakdown—of listening practices. However, changes in material arrangements also inspired new practices—pointing to the need to rethink listening practices that are merely borrowed from in-church services.